Civil Protection Model in Indonesia Through Optimizing Satlinmas - Joko Pramono; Chandra Adjie Prianggodo (Universitas Padjadjaran, 2023)
Community protection through the optimization of Satlinmas is still needed because the level of community security has not been established. The many cases of persecution, riots, fraud, conflicts, community harmony, and theft are concrete evidence that Indonesia is not yet safe. The purpose of this research is to analyze the importance of optimizing Satlinmas in the context of civil society protection in all regions, and to find out the ideal ways to optimize Satlinmas both in terms of quality and quantity. The weakness of the civil protection model through Satlinmas lies in the ineffective regulation, which makes Satlinmas less attractive. As a result, regeneration is difficult in some regions, even though Satlinmas brings a number of positive potentials to better understand the dynamics and characteristics of local communities compared to other state apparatus. The research method uses a literature study that relies on analysis and elaboration of various scientific literature in the form of journals, books, and internet literature from websites as support. The results show that the optimization of Satlinmas has not been effective, due to several obstacles. Satlinmas in some areas have not felt the welfare, even the amount of incentives is very small. There is also a delay in the distribution of incentives in some areas, which has strong implications for the low interest of the younger generation to become members of Satlinmas.